Predicting the Onset of Cavitation in Automotive Torque Converters—Part I: Designs with Geometric Similitude - D. L. Robinette; J. M. Schweitzer; D. G. Maddock; C. L. Anderson; J. R. Blough; M. A. Johnson (International Journal of Rotating Machinery)
Dimensional analysis has been applied to automotive torque converters to understand the response of performance to changes in torque, size, working fluid, or operating temperature. The objective of this investigation was to develop a suitable dimensional analysis for estimating the effect of exact geometric scaling of a particular torque converter design on the onset of cavitation. Torque converter operating thresholds for cavitation were determined experimentally with a dynamometer test cell at the stall operating condition using nearfield acoustical measurements. Dimensionless quantities based upon either speed or torque at the onset of cavitation and flow properties (e.g., pressures and temperature dependent fluid properties) were developed and compared. The proposed dimensionless stator torque quantity was found to be the most appropriate scaling law for extrapolating cavitation thresholds to multiple diameters. A power product model was fit on dimensionless stator torque data to create a model capable of predicting cavitation thresholds. Comparison of the model to test data taken over a range of operating points showed an error of 3.7%. This is the first paper of a two-part paper. In Part II, application of dimensional analysis will be expanded from torque converters with exact geometric similitude to those of more general design.